High‐Performance Red/Near‐IR Carbon Dots as Fluorescence Probes for Tumor Imaging In Vivo. Issue 23 (19th June 2018) - Yang, Sheng‐Tao; Liu, Jia‐Hui; Wang, Ping; Yang, Shengnan; Ge, Lin; Yan, Sijia; Sun, Ya‐Ping
Abstract: Carbon dots (CDots) are brightly fluorescent, especially in the same green spectral region overlapping that of the green fluorescent protein, and also benign and nontoxic. For imaging in vivo, however, red/near‐IR probes are required for the high optical transmittance through tissues and the contrast against interference from autofluorescence background. Herein, high‐performance red/near‐IR CDots are designed and prepared by modifying the core carbon nanoparticles in CDots with the incorporation of selected dye species into the nanoparticle structure. The representative modified CDots thus obtained are used as fluorescence probes in the in vivo imaging of normal and tumor‐bearing nude mice via various exposure pathways. The results suggest that these red/near‐IR CDots are indeed excellent probes for fluorescence imaging in vivo, especially with their enhanced tumor uptake. The potentially far‐reaching implications of being able to design and synthesize the modified CDots of strong optical absorptions and bright fluorescence emissions in the red/near‐IR are discussed in terms of their broad applicability to in vivo imaging and theranostics. Abstract : High‐performance red/near‐IR carbon dots (CDots) are prepared by modifying the core carbon nanoparticles in CDots with the incorporation of selected dye species into the nanoparticle structure for in vivo imaging. These red/near‐IR CDots are indeed excellent probes for fluorescence imaging in vivo, especially with their enhanced tumor uptake, thus hopeful for future theranostics applications.